2009
DOI: 10.1002/cphc.200900591
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prediction of the Hydrogen Bond Cooperativity inN‐methylacetamide Chains

Abstract: A method is proposed to rapidly predict the hydrogen bond cooperativity in N-methylacetamide chains. The parameters needed are obtained from the fittings to the hydrogen bonding energies in the formamide chains containing 2 to 8 monomeric units. The scheme is then used to calculate the individual hydrogen bonding energies in N-methylacetamide chains containing 2 to 7 monomeric units. The cooperativity predicted is in good agreement with those obtained from MP2/6-31+G** calculations by including the BSSE correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…One must have both accurate estimates of shifts of individual conformers and of relative populations in order to obtain a useful estimate of the average resonance position. The QM/MM calculated 1 H chemical shifts are systematically underestimated by ~1.4 ppm, a pattern that has been seen in studies of folded proteins as well 32,37 . The empirical SHIFTX2 models are trained to give average shifts from a single conformation, and thus have a bias towards understating conformational variability (Figure 4b).…”
Section: Resultssupporting
confidence: 52%
“…One must have both accurate estimates of shifts of individual conformers and of relative populations in order to obtain a useful estimate of the average resonance position. The QM/MM calculated 1 H chemical shifts are systematically underestimated by ~1.4 ppm, a pattern that has been seen in studies of folded proteins as well 32,37 . The empirical SHIFTX2 models are trained to give average shifts from a single conformation, and thus have a bias towards understating conformational variability (Figure 4b).…”
Section: Resultssupporting
confidence: 52%
“…3 NMA has thus been widely used to investigate the properties of the amide motif in various molecular environments both experimentally [4][5][6][7][8][9][10][11][12] and theoretically. [13][14][15][16][17][18][19] The vibrational relaxation dynamics of the amide modes of NMA have been studied before with infrared vibrational spectroscopy 8,10,[20][21][22] and with molecular dynamics simulations. 16,17,[23][24][25][26][27] All previous studies of the vibrational dynamics of NMA showed that the amide vibrations relax via intramolecular energy transfer, irrespective of the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…(1) has been established in our laboratory and has been successfully used to predict the intermolecular hydrogen bonding interactions in amide–amide, amide–thymine, and amide–uracil systems. [32–36] The first term of eq. (1) describes the dipole–dipole interaction.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…(1) to predict the intermolecular hydrogen‐bonding interactions in amide–amide, amide–thymine, and amide–uracil systems. [32–36] To further use eq. (1) to calculate the binding energies in amide–base systems in which NH···N and CH···N interactions exist, six hydrogen‐bonded amide–base dimers (Fig.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation